EVALUATION OF VEGETATIVE BARRIERS FOR WATERSHED DEVELOPMENT IN NORTH-EASTERN GHAT ZONE OF ORISSA - Rath, B.; Reddy, C.P. (Journal of Soil and Water Conservation, 2022)
Field experiments were conducted during 1993-94 and 1994-95 to evaluate the relative efficacy of three vegetative barriers viz. vetiver (Vetiveria zizanioides), thin rapier (Pennisetum purpureum) and salmi (Eulaliopsis pinata) in conserving soil and waer and increasing land productivity at Khujuripada watershed of Kandhamalr (Phulbani) district, Orissa, India. During first year, untreated control recorded the minimum soil moisture storage (11.77%) and pod yield (0.71t/ha.) of groundnut. Vetiver bunding proved as most efficient as it has enhanced soil moisture storage by 23.5% and produced 19.7% more yield than control. In the second year, untreated control resulted maximum runoff as percentage of rainfall (23%), maximum soil loss (7.5t/ha.) and the minimum grain yield of rainfed rice 3.081/ha. Among three tested vegetative barriers, vetiver bunding proved to be the most efficient vegetative barrier in conserving soil and water, reduced runoff by 20.3%, soil loss by 51.4% and increased soil moisture storage by 26.6% over control. However, there was no significant difference in respect of grain yield ofrice among three vegetative barriers and produced on an average 1 t/ha. (32.5%) more rice yield when compared to yield obtained from untreated control. Considering the overall performance, ease of establishment and maintenance, vetiver bunding may be recommended as best vegetative barrier for watershed development in North-Eastern Ghat Zone of Orissa.